2017
DOI: 10.3389/fnagi.2017.00192
|View full text |Cite
|
Sign up to set email alerts
|

Results of an Interdisciplinary Day Care Approach for Chronic Tinnitus Treatment: A Prospective Study Introducing the Jena Interdisciplinary Treatment for Tinnitus

Abstract: Objective: Considering the heterogeneity of the symptoms shown by patients suffering from chronic tinnitus, there are surprisingly few interdisciplinary treatments available, and mostly available only for inpatients. In order to provide an interdisciplinary treatment, we developed a day care concept in which each patient was treated by an ENT doctor, a cognitive behavioral therapist, a specialist for medical rehabilitation and an audiologist (Jena Interdisciplinary Treatment for Tinnitus, JITT). The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 86 publications
(125 reference statements)
1
6
0
2
Order By: Relevance
“…The study joins previous research on self-reported symptom-relief following hearing aid fittings in patients with hearing loss [ 19 , 20 , 47 ] with possible mechanisms involving enhancements of individuals’ tonal environments [ 21 , 48 , 49 ], tinnitus masking [ 19 ], reduced tinnitus awareness and improved communication opportunities [ 22 ] or possible psychological effects such as, for some patients, enhanced senses of self-efficacy, control, or social inclusion. In the present study, the majority of participants (68%) wore the hearing aids between 5.25 and 13.41 h/day, which is broadly consistent with the previously reported times in the literature (e.g., 3.67–11.93 h/day [ 50 ], 5.49–11.77 h/day [ 51 ], or 1.20–11.00 h/day [ 52 ]).…”
Section: Discussionsupporting
confidence: 91%
“…The study joins previous research on self-reported symptom-relief following hearing aid fittings in patients with hearing loss [ 19 , 20 , 47 ] with possible mechanisms involving enhancements of individuals’ tonal environments [ 21 , 48 , 49 ], tinnitus masking [ 19 ], reduced tinnitus awareness and improved communication opportunities [ 22 ] or possible psychological effects such as, for some patients, enhanced senses of self-efficacy, control, or social inclusion. In the present study, the majority of participants (68%) wore the hearing aids between 5.25 and 13.41 h/day, which is broadly consistent with the previously reported times in the literature (e.g., 3.67–11.93 h/day [ 50 ], 5.49–11.77 h/day [ 51 ], or 1.20–11.00 h/day [ 52 ]).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, several previous studies have not included tinnitus patients with psychiatric co-morbidity. While this might allow for more homogeneous samples, it is not congruent with the clinical realities of tinnitus not only being associated with subjective distress but also manifest psychopathologies (Durai and Searchfield, 2016; Ivansic et al, 2017; Jacques et al, 2013; Pattyn et al, 2016; Trevis et al, 2016; Ziai et al, 2017). Even though our study aimed at addressing this factor, we need to consider the limitation that our choice of psychiatric controls mostly included depression/anxiety disorder patients (to match this particular tinnitus sample), so expansion to other psychopathology dimensions is warranted.…”
Section: Discussionmentioning
confidence: 97%
“…The two tinnitus groups (total of n = 59 patients) included patients with chronic, bilateral tinnitus with a duration of more than three months. Patients were recruited from the specialised interdisciplinary tinnitus entre (Ivansic et al, 2017) of the Department for Otorhinolaryngology in Jena, were they had undergone extensive medical investigation before taking part in the study. Most of the tinnitus patients suffered from hearing loss (4-pure tone average (4-PTA) > 25 dB in pure tone audiogram).…”
Section: Methodsmentioning
confidence: 99%
“…There is significant evidence to suggest that tinnitus is not just an abnormality in the auditory pathway. The distress and functional declines associated with tinnitus are not only a function of the perceived loudness of the percept (39). Tinnitus-related distress is associated with depression, anxiety, and somatic symptom severity (40).…”
Section: Limbic Pathway Pathophysiologymentioning
confidence: 99%